Room-temperature direct arylation of anilides under external oxidant-free conditions using CO2-Derived Dimethyl Carbonate (DMC) as a 'green' solvent - Sahoo, Manoj K.; Rana, Jagannath; Subaramanian, Murugan; Balaraman, Ekambaram (Chemistryselect, 2017)
Here, an efficient catalytic protocol for direct C-H bond arylation of anilides under base- and external oxidant-free conditions is reported. This reaction proceeds readily at room temperature using CO2-derived dimethyl carbonate (DMC) as a green solvent under visible-light dual catalysis. Later, application of our strategy for the gram-scale synthesis of Boscalid has been successfully shown. An unprecedented unsymmetrical bis-arylation of anilides is also demonstrated under mild, redox-neutral conditions.

Reusable cobalt catalyst for reversible acceptorless dehydrogenation and hydrogenation of N-Heterocycles - Jaiswal, Garima; Subaramanian, Murugan; Sahoo, Manoj K.; Balaraman, Ekambaram (ChemCatChem, 2019)
<span style="color: rgb(42, 45, 53); font-family: "Source Sans Pro", Arial, Helvetica, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(248, 248, 248);">The development of robust catalytic systems based on basemetals for reversible acceptorless dehydrogenation (ADH) and hydrogenation of feedstock chemicals is very important in the context of ` hydrogen storage'. Herein, we report a highly efficient reusable cobalt-based heterogeneous catalyst for reversible dehydrogenation and hydrogenation of N-heterocycles. Both the ADH and the hydrogenation processes operate under mild, benign conditions.

Room temperature catalytic dehydrogenation of cyclic amines with the liberation of H-2 using water as a solvent - Sahoo, Manoj K.; Balaraman, Ekambaram (Green Chemistry, 2019)
Catalytic dehydrogenation of cyclic amines, in particular partially saturated N-heterocycles to N-heterocyclic arenes, with the removal of molecular hydrogen as the sole byproduct in water is reported. This dehydrogenation reaction proceeds smoothly under very mild and benign conditions and operates at room temperature. This distinctive reactivity has been achieved under dual catalytic conditions by merging the visible-light active [Ru(bpy)(3)](2+) as the photoredox catalyst and a newly synthesized cobalt complex as the proton-reduction catalyst. A detailed mechanistic study (control experiments, electrochemical studies, UV-visible experiments) is presented for the present dual catalysis.